2000
DOI: 10.1021/la000851k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Gradients of Proteins on Surfaces with Microfluidic Networks

Abstract: The capability of microfluidic networks to pattern substrates with proteins is extended to create density gradients of proteins on surfaces. The networks are micromachined in Si, and the substrates are hydrophobic poly(dimethylsiloxane) (PDMS) elastomers. The gradients result from the progressive depletion of proteins in the fluids due to their adsorption onto the PDMS substrate as the solution travels along the microchannel. Forming gradients of rhodamine-tagged antigens on PDMS and binding the antigens with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…The long incubation times in conventional IHC, which are in the range of 30 min to hours, may well result in a marked loss of proportionality between antigen expressions in the tissue and the immunohistochemical signal, as the antibody binding may be hindered by saturation phenomena according to Langmuir's isotherm, by steric hindrance (20), diffusion-limited transport of the antibodies to the surface (19,20,22,(28)(29)(30)(31)(32)(33)(34), or a combination of these factors. Caelen et al (35) performed an experiment in which fluorescently labeled target antigens were immobilized on a surface with different concentrations and incubated with another fluorescent marker-labeled detection antibody in a bulk solution during 30 min, as done in a conventional IHC protocol. They found that the fluorescent signal originating from target antigens immobilized on the surface was not linearly proportional to that of the bound detection antibody, but that the signal of bound detection antibodies saturated after a given target antigen concentration, resulting in overstaining of the midconcentration range and understaining of the high-concentration range of the immobilized target antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The long incubation times in conventional IHC, which are in the range of 30 min to hours, may well result in a marked loss of proportionality between antigen expressions in the tissue and the immunohistochemical signal, as the antibody binding may be hindered by saturation phenomena according to Langmuir's isotherm, by steric hindrance (20), diffusion-limited transport of the antibodies to the surface (19,20,22,(28)(29)(30)(31)(32)(33)(34), or a combination of these factors. Caelen et al (35) performed an experiment in which fluorescently labeled target antigens were immobilized on a surface with different concentrations and incubated with another fluorescent marker-labeled detection antibody in a bulk solution during 30 min, as done in a conventional IHC protocol. They found that the fluorescent signal originating from target antigens immobilized on the surface was not linearly proportional to that of the bound detection antibody, but that the signal of bound detection antibodies saturated after a given target antigen concentration, resulting in overstaining of the midconcentration range and understaining of the high-concentration range of the immobilized target antigen.…”
Section: Discussionmentioning
confidence: 99%
“…D) Fluorescence micrograph showing short-scale gradients of TRITC-labeled (TRITC: tetramethyl rhodamine isothiocyanate) Abs that were deposited using an MFN in PDMS onto a glass surface. (Adapted with permission from [175,178]. Copyright 2000, American Chemical Society.…”
Section: Transporting Liquids In Microchannelsmentioning
confidence: 99%
“…2D). [8,[178][179][180][181] Interestingly, the length scales and diffusion times found in microchannels compare with biochemical processes occurring in living cells. [19,182,183] The ratio between convective and diffusive transport is measured by the (dimensionless) Péclet number:…”
Section: Patterning Of Surfaces Using Microfluidicsmentioning
confidence: 99%
“…The test mixture of acidic proteins, BSA and b-lactoglobulin, were separated on three-layer PVA(88)-coated PDMS microchip with a good resolution at pH 8 ( Fig. 8) but BSA was strongly adsorbed on original PDMS and used as a protecting coating [38]. Using the low-viscosity separation matrix 2% HPMC (50 cP), FX174 RF/HaeIII fragments can be easily resolved within 400 s (Fig.…”
Section: Some Applicationsmentioning
confidence: 99%